A linguistic complexity pattern that defies aging: The processing of multiple negations. (May 2021) - Grodzinsky, Yosef; Behrent, Kim; Agmon, Galit; Bittner, Nora; Jockwitz, Christiane; Caspers, Svenja; Amunts, Katrin; Heim, Stefan
Abstract: We know that linguistic ability tends to diminish in aging. The question we addressed was whether it is selectively affected, and if so, whether aging affects sentence processing in the same way it affects other cognitive abilities. To this end, we conducted a fine-grained investigation into a critical aspect of sentences – the number of negations they contain. We studied the processing costs of multiple negations in a cross-sectional design with 105 healthy aging participants who performed a truth-value judgement task. Quantifier-containing sentences with 0, 1 or 2 negations were juxtaposed to images with arrays of blue and yellow circles. This design enabled us to assess the cost of negation from a novel perspective. In parallel, we tested these participants on standard measures of cognitive aging. In addition to the typical slowing caused by aging, and by an added negation, we found that aging effects were restricted: they did not accumulate with the number of negations. Rather, processing speed in the conditions with one negation ( negative statements) were affected by aging, whereas it was unaffected in conditions with an even number (zero/two) of negations ( positive statements). We conclude that aging affects negation processing in a manner determined by its total negativity value of a sentence ( a k a monotonicity), not the number of negations it contains. Our findings challenge both the idea of global incremental processing-cost, and of non-specific cognitive slowing in aging. That is, the cost of processing, as well as the course of the aging of the sentence processor are constrained by highly specific linguistic considerations. Highlights: Aging (that otherwise slows down processing) does not affect the processing of double negation. We found that the processing costs of multiple negations is not incremental. These surprising results come from combined psycholinguistic and aging-related work. We tested a group of 105 aging individuals were tested on standard cognitive tests. We used a picture verification paradigm (sentences about proportion with and without 0, 1, 2 negations followed by proportion depicting images). Most theories of negation processing do not discuss multiple negations as a special case. Most theories of aging likewise view more complex input materials as more cognitively taxing. Our results pose a challenge to both, and are therefore of great significance to the field, we believe.